2019
DOI: 10.1016/j.actbio.2019.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of human epidermal stem cells on undulating elastomer substrates reflects differences in cell stiffness

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
2
42
1
Order By: Relevance
“…Given accumulating evidence of nuclear mechano-transduction processes 27,39-41 we then investigated how these physical changes translated into mechano-responses and biochemical changes within the cells as a function of local curvature. We showed that the patterns of cellular densities generated by the matrix curvature are associated with significant changes in the spatial distribution of YAP 2,3 , consistent with the idea of curvature-sensing occurring via physically-driven thickness/density-changes. YAP in particular has been shown to be is a key transcription factor that mediates the interplay between cellular mechanics and signaling cascades underlying gene expression, cell proliferation, differentiation fate decisions, and organ development.…”
Section: Discussionsupporting
confidence: 79%
“…Given accumulating evidence of nuclear mechano-transduction processes 27,39-41 we then investigated how these physical changes translated into mechano-responses and biochemical changes within the cells as a function of local curvature. We showed that the patterns of cellular densities generated by the matrix curvature are associated with significant changes in the spatial distribution of YAP 2,3 , consistent with the idea of curvature-sensing occurring via physically-driven thickness/density-changes. YAP in particular has been shown to be is a key transcription factor that mediates the interplay between cellular mechanics and signaling cascades underlying gene expression, cell proliferation, differentiation fate decisions, and organ development.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, their action could be affected by direct interactions with key lipids within membranes or by changes in their local environment due to lipid variation. Lipid composition can affect the stiffness and mechanosensitivity of plasma membranes ( 44 46 ), and differences in the stiffness of epidermal stem cells and neighboring basal cells in culture were recently reported ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human BM exhibits undulations and epidermal stem cell patterning is dependent on mechanical forces exerted at intercellular junctions. Cell density is highest, and thus cell-matrix adhesion area the lowest, at the bases of undulations, whereas stem cells accumulate at tips (Helling et al 2019;Mobasseri et al 2019).…”
Section: Matrix Rigidity and Topologymentioning
confidence: 99%